2008
DOI: 10.1111/j.1467-7679.2008.00407.x
|View full text |Cite
|
Sign up to set email alerts
|

Does Supermarket Purchase Affect the Dietary Practices of Households? Some Empirical Evidence from Guatemala

Abstract: Very little is known about how changes in the retail environment affect consumers’diet and health status, especially in developing countries. This article examines the impact of supermarket purchases on the dietary practices of households in Guatemala, using an instrumental variable method to take account of the potential endogeneity of the supermarket purchase variable. The results reveal that supermarket purchases increase the share of highly and partially processed foods at the expense of staple foods, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
106
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(131 citation statements)
references
References 31 publications
(34 reference statements)
21
106
1
3
Order By: Relevance
“…The two studies which the authors have identified which pursue a similar analysis have been carried out in Tunisia and Guatemala (Asfaw, 2008;Tessier et al, 2008). These studies reported conflicting findings with the Tunisian research reporting that regular supermarket shopping was associated with a slight improvement in overall dietary quality, while the Guatemalan study found that purchasing more of food at a supermarket was associated with increased intake of highly and partially processed foods and a higher BMI.…”
mentioning
confidence: 64%
“…The two studies which the authors have identified which pursue a similar analysis have been carried out in Tunisia and Guatemala (Asfaw, 2008;Tessier et al, 2008). These studies reported conflicting findings with the Tunisian research reporting that regular supermarket shopping was associated with a slight improvement in overall dietary quality, while the Guatemalan study found that purchasing more of food at a supermarket was associated with increased intake of highly and partially processed foods and a higher BMI.…”
mentioning
confidence: 64%
“…The impact of the food retail environment on consumers' dietary behaviour is a complex issue (14) . Some researchers argue that supermarkets in developing countries typically provide cheap, processed and junk foodstuffs, which suggests that the growth of supermarkets is a driver of the transition towards diets high in energy and nutrient-poor foods (15,16) . Likewise, fast food is gaining popularity among younger generations and is widely spreading over both traditional and *Corresponding author: Email xiaoyong.zhang@wur.nl r The Authors 2011 non-traditional food outlets (17,18) .…”
Section: Introductionmentioning
confidence: 99%
“…To some extent, these shifts are 4 due to rising incomes, urbanization, and changes in people's preferences and lifestyles. However, global advertising of food companies and the rapid spread of supermarkets, fast food chains, and other modern retail outlets probably also contribute to the observed changes in shopping behavior and consumption patterns (Reardon et al, 2003;Hawkes, 2008;Asfaw, 2008;Timmer, 2009). Modern retail outlets tend to offer a greater variety of processed foods, sometimes at lower prices, at least when converted to the price per calorie consumed (Reardon et al, 2003;Rischke et al, 2014).…”
Section: Dietary Trends and Child Nutrition: Expected Relationshipsmentioning
confidence: 99%